2019
DOI: 10.1042/bsr20192803
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and antifungal activity of a plant peptide expressed in the interaction between Capsicum annuum fruits and the anthracnose fungus

Abstract: Plant defensins are low molecular weight basic peptides ranging from 5 to 7 kDa, with capacity of inhibiting various pathogens, including fungi. They are present in different tissues of plants, including floral parts and fruits of Capsicum sp. The IIF48 extract, present in immature fruits of Capsicum annuum inoculated with C. gloeosporioides, was able to inhibit up to 100% growth ‘in vitro’ of the fungus Colletotrichum gloeosporioides. The main objective of this work was the purification and antifungal activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…Thus, 20 ml of each extract concentration was incorporated separately under aseptic conditions into 200 ml of molten potato dextrose agar (PDA) medium. In this experiment, four concentrations (10,20,30, and 60%) of the aqueous seed extract were tested for their e cacy. After 10 ml of poisoned medium was poured into separate sterile Petri dishes, a one-disc plug (Ø 0.5 cm) of B. cinerea (from a 4-day-old culture) was placed in the center of the poisoned medium.…”
Section: In Vitro Evaluation Of the Activity Of The Aqueous Seed Extr...mentioning
confidence: 99%
“…Thus, 20 ml of each extract concentration was incorporated separately under aseptic conditions into 200 ml of molten potato dextrose agar (PDA) medium. In this experiment, four concentrations (10,20,30, and 60%) of the aqueous seed extract were tested for their e cacy. After 10 ml of poisoned medium was poured into separate sterile Petri dishes, a one-disc plug (Ø 0.5 cm) of B. cinerea (from a 4-day-old culture) was placed in the center of the poisoned medium.…”
Section: In Vitro Evaluation Of the Activity Of The Aqueous Seed Extr...mentioning
confidence: 99%
“…Other studies reported the prospective use of AMPs against various bacteria ( Fensterseifer et al, 2015 ) and fungi ( Maracahipes et al, 2019 ; dos Santos-Silva et al, 2021 ), indicating their potential as a new therapeutic approach in the treatment of local and systemic infections, including those against bacteria multi-resistant to antibiotics ( Almaaytah et al, 2017 ). The authors highlighted the need to use robust methodologies to identify and circumvent the possible side effects that may appear in the interactions of these molecules.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…17 The pepper genus Capsicum is a promising source of AMPs, including defensins, with a wide range of inhibitory actions. [18][19][20] However, few investigations have been conducted to identify and analyze defensins in Capsicum chinense. In previous studies, Resende et al, 21 obtained a fraction rich in peptides called the G3 fraction, which inhibited the growth of fungi of the genera Colletotrichum and Fusarium.…”
Section: Introductionmentioning
confidence: 99%